Effectiveness and Feasibility of Enteral Nutrition Practice Guidelines in Patients Hospitalized in Medical Ward - เลาหธนาคม สุกัญญา (Journal of Health Science of Thailand, 2023)
This study aimed to develop a clinical practice guidelines (CPGs) and examine the effectiveness of implementing for enteral feedings in Medical ward 3, Lampang Hospital. Participants in this study included 39 patients who were admitted prior to the implementing of CPGs from December 2019 to February 2020, and those 39 patients who admitted during the implementation from April to June 2020. Participants also included 19 nurses, and 9 doctors who used the CPGs. This CPGs was developed based on the Australian National Health and Medical Research Council and the Society of Parental and Enteral Nutrition of Thailand: SPENT levels of evidence and grades of recommendation. The instruments used to collect data relating to the CPGs for enteral feeding consisted of four parts: (1) the nutrition monitoring form, (2) the gastric residual volume (GRV) monitoring form, (3) the guideline nurse feasibility questionnaire, and (4) the physician feasibility questionnaire. Three experts evaluated the CPGs for validity (CVI=0.87), and Cronbach alpha was equal to 0.80. Descriptive statistics, percentages, means, and independent t-tests were used to analyze the data. The CPGs were divided into six domains: (1) nutritional screening and assessment, (2) indicators and time to start enteral feeding, (3) how to start enteral feeding, (4) physician-assisted nutrition therapy, (5) enteral nutrition, and (6) drug administration through enteral feeding. Findings showed that there was higher proportion of referrals to a nutritionist for enteral feeling regiment adjustment among patients in the clinical practice group (p<0.05). In addition, the albumin level, total lymphocyte count and hemoglobin of the CPG group were increased, whereas the albumin levels of the pre-clinical practice group decreased (p<0.05). As a result, all moderate to severe malnutrition patients in the CPG group whose intravenous feeding complete within the first 24 hours had no refeeding syndrome, complications, and a shorter endotracheal tube duration (p<0.05); although, the average cost in the patients in the CPGs group was higher. The possibility of using CPGs of nurses and doctors was 89.47 percent and 95.77 percent, respectively. Thus, clinical practice guideline for tube-fed patients’ nutritional care provided agencies with appropriate screening for malnutrition risk and therapy. Further, collaboration from multidisciplinary healthcare professionals can improve patient’s nutrition. It is recommended to scale-up the use of the CPG to other clinical wards.